Precontractual Investigation and Sequential Screening - Stefan Terstiege (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
Should contract design induce an agent to conduct a precontractual investigation even though, in any case, the agent will become fully informed after the signing of the contract? This paper shows that imperfect investigations might be encouraged. The result stands in contrast to previous studies, which focus on perfect investigations. The contrast exists because if precontractual investigation is perfect, the benefits of sequential screening vanish.
urn:nbn:de:bvb:19-epub-17334-5
Keywords: D82; D83; D86; 330; Principal agent; information acquisition; sequential screening